ADDITION OF DURIAN PEEL IN CATTLE RATIONS TO IMPROVE DRY MATTER AND ORGANIC DIGESTIBILITY - Soraya Faradila; Syamsuddin; Fitriana Akhsan; Ita Nurhidaya Safitri; Rosa Ure Inadai Mangun Illodo (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
The utilization of agricultural and plantation waste serves as an alternative solution to overcome farmers’ challenges in providing ruminant feed. With the peel composition reaching 60–70% of the total fruit mass, durian generates a significant amount of waste that can be used as livestock feed. Identifying potential feed sources in terms of quality, quantity, and continuity is essential to ensure the availability of feed for beef cattle. The objective of this study was to determine the digestibility of cattle rations supplemented with durian peel. This study employed a completely randomized design with four treatments and three replications. The treatments consisted of a control ration (100% basal ration without durian peel), basal ration with 10% durian peel, basal ration with 15% durian peel, and basal ration with 20% durian peel. The parameters observed were dry matter digestibility (DMD) and organic matter digestibility (OMD), which were analyzed using an in vitro method. The results indicated that the control treatment differed significantly (P<0.05) from the other treatments, and increasing levels of durian peel supplementation led to higher digestibility. The conclusion of this study is that the addition of 20% durian peel to the ration optimizes dry matter and organic matter digestibility in the rumen of cattle. Further in vivo studies are required.